Study guides

☆☆

Q: How do you factor 6x2 plus 12x plus 4?

Write your answer...

Submit

Still have questions?

Related questions

(3x+1)(2x+4) = 6x2+4+2x+12x = 6x2+14x+4

3x(x2 + 2x - 4)

3x(x2 + 2x - 4)

3x3+12x = 3x(x2+4)

First take out the common factor (4):4(6x2 + 2x + 1)6x2 + 2x + 1 cannot be factored, so 4(6x2 + 2x + 1) is as far as you can get with factoring.

(3x + 4)(2x - 1)

x2 + 12x + 32 = (x + 8)(x + 4)

(x + 4)(x + 8)

x2 + 12x + 32 = (x + 4)(x + 8)

4(x + 2)(x + 1)

(3x + 5)(3x^2 + 4)

2(x + 4)(x + 2)

The expression may be : 6x2 + 17x + 12 This factors as, 6x2 + 17x + 12 = (3x + 4)(2x + 3) Or, the expression could be : 6x2 - 17x + 12 This factors as, 6x2 - 17x + 12 = (3x - 4)(2x - 3)

x(x + 4)(x - 3)

(x - 8)(x - 4)

16X + 12X all I can see here is factoring out a 4X factor 4X(4 + 3) ---------------

(3x-4)(2x+5) x=4/3 or -5/2

If that's -17x, it factors to (3x - 4)(2x - 3)

No.

(x + 8)(x + 4)

9x2 + 12x + 4 = 9x2 + 6x + 6x + 4 = 3x(3x + 2) + 2(3x + 2) = (3x + 2)(3x + 2) = (3x + 2)2

2(3x2 - 2)

(x + 8)(x + 4)

(3x - y+ 2)(3x + y + 2)

x2 + 12x + 32 = x2 + 8x + 4x + 32 = x*(x + 8) + 4*(x + 8) = (x + 8)*(x + 4)